RELEVANCE OF VARIATION OF LIVER FUNCTION TESTS IN PREGNANCY INDUCED HYPERTENSION - DIPTI MOHAPATRA; MANASI BEHERA (International Journal of Pharma and Bio Sciences, 2013)
Pregnancy induced hypertension is one of the most common and challenging medical complication of pregnancy as this complex disease continues to defeat all efforts to bring about satisfactory and rewarding policy of management because of its poor understanding of pathological basics. It is the hypertension that results from direct gravid state and is one of the critical obstetric complications attributing to high incidence of fetal and maternal morbidity and mortality. This complication of pregnancy though responsible for large number of maternal and perinatal deaths, can be easily prevented and controlled by early detection of disease and proper management. In this study, we assessed the extent to which liver function tests can be used to predict the adverse maternal outcomes.